Lecture 3 State-Space Solutions and Realization - v1
Lecture 3 State-Space Solutions and Realization - v1
Lecture 3 State-Space Solutions and Realization - v1
The solution of (1)-(2) can be computed with the aid of Laplace transform.
One has
e At = L−1 [(sI − A)−1 ]
Find e At , where
0 −1
A=
1 −2
f (−1) = h(−1) : e −t = β0 − β1
f 0 (−1) = h0 (−1) : te −t = β1
Thus we have
h(λ) = e −t + te −t + te −t λ
So
e At = h(A) = (e −t + te −t )I + te −t A
−t
e + te −t −te −t
=
te −t e −t − te −t
Method 2:
−1
−1 s 1 1 s + 2 −1
(sI − A) = = 2
−1 s + 2 s + 2s + 1 1 s
" #
s+2 1
(s+1)2
− (s+1)2
= 1 s
(s+1)2 s+1)2
(1 + t)e −t −te −t
At −1 −1
e = L [(sI − A) ]=
te −t (1 − t)e −t
(1 + t)e −t −te −t
−1 −1
L [(sI − A) ] =
te −t (1 − t)e −t
W. Dong (UTRGV, Dept. of ECE) 7 / 75
Example
Solution:
Z t
At
x(t) = e x(0) + e A(t−τ ) Bu(τ )dτ
0
(1 + t)e −t −te −t
= x(0)
te −t (1 − t)e −t
Rt
− 0 (t − τ )e −(t−τ ) u(τ )dτ
+ R t −(t−τ ) u(τ )dτ
0 [1 − (t − τ )]e
Method 2: Let
one has
Z kT
x[k] = x(kT ) = e AkT x(0) + e A(kT −τ ) Bu(τ )dτ
0
Z (k+1)T
x[k + 1] = e AT x[k] + e A(kT +T −τ ) Bdτ u[k]
kT
ZT
= e AT x[k] + e Aα Bdαu[k], α = kT + T − τ
0
x[k + 1] = Ad x[k] + Bd u[k] (6)
y [k] := y (kT ) = Cx(kT ) + Du(kT ) = Cd x[k] + Dd u[k] (7)
where
Ad = e AT (8)
Z T Z T
Aτ −1
Bd = e dτ B = A de Aτ B
0 0
= A−1 (e AT − I )B = A−1 (Ad − I )B, if A is nonsingular (9)
Cd = C (10)
Dd = D (11)
˙
x̄(t) = Āx̄(t) + B̄u(t) (18)
y (t) = C̄ x̄(t) + D̄u(t) (19)
where
Ā = PAP −1 , B̄ = PB, C̄ = CP −1 , D̄ = D (20)
is said to be (algebraically) equivalent to (16)-(17) and x̄ = Px is called
an equivalence transformation.
W. Dong (UTRGV, Dept. of ECE) 15 / 75
Equivalent State Equations
Two state equations are said to be zero-state equivalent if they have the
same transfer matrix or
Theorem 2
Two linear time-invariant state equations {A, B, C , D} and {Ā, B̄, C̄ , D̄}
are zero-state equivalent or have the same transfer matrix if and only if
D = D̄ and
CAm B = C̄ Ām B̄, m = 0, 1, 2, . . .
Proof: Noting
(1 − s −1 λ)−1 = 1 + s −1 λ + s −2 λ2 + · · ·
s −1 (1 − s −1 λ)−1 = s −1 + s −2 λ + s −3 λ2 + · · ·
(sI − A)−1 = s −1 (I − s −1 A)−1 = s −1 I + s −2 A + s −3 A2 + · · ·
D+CBs −1 +CABs −2 +CA2 Bs −3 +· · · = D̄+C̄ B̄s −1 +C̄ ĀB̄s −2 +C̄ Ā2 B̄s −3 +· · ·
for any s. Compare the coefficients of s −i , the theorem is proved.
Figure 1: A circuit
Let x1 be the current through the inductor and x2 be the voltage over the
capacitor. For the two loops, by KVL,
−u + ẋ1 + x2 = 0, 1(ẋ2 − x1 ) + x2 = 0
So
ẋ1 0 1 1
= x+ u = Ax + Bu
ẋ2 1 −1 0
y = [0, 1]x = Cx
W. Dong (UTRGV, Dept. of ECE) 20 / 75
Example
If we choose two mesh currents as x̄1 and x̄2 , then
So
x̄˙ 1
−1 1 1
= x̄ + u = Āx̄ + B̄u
x̄˙ 2 −1 0 0
y = [1, −1]x̄ = C̄ x̄
For simplicity, we consider a 4-th order SISO LTI causal system with the
equation
ẋ = Ax + bu
y = Cx + du
Two canonical forms will be considered: companion form and modal form.
where
0 0 0 β1
1 0 0 β2
Ā = PAP −1 = Q −1 AQ =
0 1 0 β3
0 0 1 β4
is the companion form.
The MATLAB command is: [ab,bb,cb,db,P]=canon(a,b,c,d,’companion’)
W. Dong (UTRGV, Dept. of ECE) 23 / 75
Modal form
Theorem 3
A transfer matrix C(s) is realizable if and only if C(s) is a proper rational
matrix.
1
Ĝ (s) = C (sI − A)−1 B + D = C [Adj(sI − A)]B + D (24)
det(sI − A)
Ĝ (∞) = D (25)
d(s) = s r + α1 s r −1 + · · · + αr −1 s + αr
be the least common denominator of all entries of Ĝsp (s). Here we require
d(s) to be monic; that is, its leading coefficient is 1. Then Ĝsp (s) can be
expressed as
1 1
Ĝsp (s) = [N(s)] = [N1 s r −1 + N2 s r −2 + · · · + Nr −1 s + Nr ] (26)
d(s) d(s)
By (29),
sZ = AZ + B (31)
which means that
sZ1 = −αZ1 − α2 Z2 − · · · − αr Zr + Ip
So,
α2 αr
sZ1 = −α1 Z1 − Z1 − · · · − r −1 Z1 + Ip
s s
α2 αr
= − α1 + + · · · + r −1 Z1 + Ip
s s
α2 αr d(s)
s + α1 + + · · · + r −1 Z1 = r −1 Z1 = Ip
s s s
s r −1 s r −2 1
Z1 = Ip , Z2 = Ip , . . . , Zr = Ip ,
d(s) d(s) d(s)
So,
1
C (sI −A)−1 B + Ĝ (∞) = [N1 s r −1 +N2 s r −2 +· · ·+Nr ]+ Ĝ (∞) = Ĝsp (s)
d(s)
1 1
Ĝsp (s) = [N(s)] = [N1 s r −1 + N2 s r −2 + · · · + Nr −1 s + Nr ](32)
d(s) d(s)
Solution:
−6(s + 2)2 3(s + 2)(s + 0.5)
2 0 1
Ĝ (s) = +
0 0 s 3 + 4.5s 2 + 6s + 2 0.5(s + 2) (s + 1)(s + 0.5)
2 0 1 −6 3
= + 3 s 2+
0 0 s + 4.5s 2 + 6s + 2 0 1
−24 7.5 −24 3
s+
0.5 1.5 1 0.5
MATLAB commands:
num1=[4,-2,-20;0,0,1]; den1=[2,5,2]; [a1,b1,c1,d1]=tf2ss(num1,den1)
num2=[3,6;1,1]; den2=[1,4,4]; [a2,b2,c2,d2]=tf2ss(num2,den2)
sys1=ss(a1,b1,c1,d1); sys2=ss(a2,b2,c2,d2);
or
−2.5 −1 0 0 1 0
1 0 0 0 0 0
ẋ = = x + u (41)
0 0 −4 −4 0 1
0 0 1 0 0 0
−6 −12 3 6 2 0
y = x+ u (42)
0 0.5 1 1 0 0
Consider
ẋ = A(t)x (43)
where A(t) is n × n with continuous functions of t as its entries.
Lemma 4
For each initial state xi (t0 ), there exists a unique solution xi (t), for
i = 1, 2, . . . , n. If x1 (t0 ), x2 (t0 ), . . . , xn (t0 ) are linearly independent, then
the columns of X (t) = [x1 (t), x2 (t), . . . , xn (t)] are linear independent for
any t ≥ t0 .
x(t1 ) = X (t1 )v = 0
Properties of Φ(t, t0 ):
1 Φ(t, t) = I
2 Φ−1 (t, t0 ) = Φ(t0 , t)
3 Φ(t, t0 ) = Φ(t, t1 )Φ(t1 , t0 )
4 x(t) = Φ(t, t0 )x(t0 ) for any t and t0 .
Theorem 5
Consider the system
Proof:
Z t
∂ ∂
ẋ(t) = Φ(t, t0 )x(t0 ) + Φ(t, τ )B(τ )u(τ )dτ
∂t ∂t t0
Z t
∂
= A(t)Φ(t, t0 )x(t0 ) + Φ(t, τ )B(τ )u(τ ) dτ
t0 ∂t
+Φ(t, t)B(t)u(t)
Z t
= A(t)Φ(t, t0 )x(t0 ) + (A(t)Φ(t, τ )B(τ )u(τ )) dτ + B(t)u(t)
t0
= A(t)x(t) + B(t)u(t)
y (t) = C (t)x(t) + D(t) = · · ·
where
G (t, τ ) is the impulse response matrix and is the output at time t excited
by an impulse input applied at time τ .
• If A(t) is a constant,
and X (t) = e At .
0.25t 2 + 1 −0.5
−1
X (t) =
−0.25t 2 0.5
W. Dong (UTRGV, Dept. of ECE) 54 / 75
Example
0.25t 2 + 1 −0.5
−1 1 1
Φ(t, t0 ) = X (t)X (t) =
0.5t 2 0.5t 2 + 2 −0.25t 2 0.5
1 0
=
0.5(t 2 − t02 ) 1
for k = k0 , k0 + 1, . . . , .
It can be shown that
and
Φ[k, k0 ] = Φ[k, k1 ]Φ[k1 , k0 ]
W. Dong (UTRGV, Dept. of ECE) 56 / 75
Discrete-Time Case
where
G [k, m] = C [k]Φ[k, m + 1]B[m] + D[m]δ[k − m]
is the impulse response sequence.
d
[P(t)x(t)] = Ṗ(t)x(t) + P(t)ẋ(t) = Ṗ(t)x(t) + P(t)A(t)x(t)
dt
+P(t)B(t)u(t)
= [Ṗ(t) + P(t)A(t)]x(t) + P(t)B(t)u(t)
= [Ṗ(t) + P(t)A(t)]P −1 (t)x̄(t) + P(t)B(t)u(t)
y (t) = C (t)P −1 (t)x̄(t) + D(t)u(t)
So,
˙
x̄(t) = Ā(t)x̄(t) + B̄(t)u(t) (56)
y (t) = C̄ (t)x̄(t) + D̄(t)u(t) (57)
where
d
[P(t)X (t)] = Ṗ(t)X (t) + P(t)Ẋ (t) = Ṗ(t)X (t) + P(t)A(t)X (t)
dt
= [Ṗ(t) + P(t)A(t)]X (t)
= [Ṗ(t) + P(t)A(t)]P −1 (t)X̄ (t) = Ā(t)X̄ (t)
Theorem 6
Let A0 be an arbitrary constant matrix. Then there exists an equivalence
transformation that transforms (54) into (56) with Ā(t) = A0 .
Ẋ −1 X + X −1 Ẋ = 0
Ẋ −1 = −X −1 Ẋ X −1 = −X −1 A
Let
P(t) := e A0 t X −1
then
Ā = [PA + Ṗ]P −1
= [e A0 t X −1 A + A0 e A0 t X −1 + e A0 t Ẋ −1 ]Xe −A0 t
= A0 e A0 t X −1 Xe −A0 t = A0
W. Dong (UTRGV, Dept. of ECE) 62 / 75
Equivalent Time-Varying Equations
If A0 = 0, then
Ā = 0, B̄ = X −1 B, C̄ = CX , D̄ = D (59)
The block diagrams of (54) with A(t) 6= 0 and A(t) = 0 are plotted in
Figure 3. The block diagram with A(t) = 0 has no feedback and is
considerably simpler. Every time-varying state equation can be
transformed into such a block diagram. However, in order to do so. its
fundamental matrix should be known.
The impulse response matrix of (56) is, using (58) and (59),
Definition 7
A matrix P(t) is called a Lyapunov transformation if P(t) is nonsingular,
P(t) and Ṗ(t) are continuous, and P(t) and P −1 are bounded for all t.
Equations (54) and (56) are said to be Lyapunov equivalent if P(t) is a
Lyapunov transformation.
Theorem 8
Consider (54) with A(t) = A(t + T ) for all t and some T > 0. Let X (t)
be a fundamental matrix of ẋ = A(t)x. Let Ā be the constant matrix
computed from e ĀT = X −1 (0)X (T ). Then (54) is Lyapunov equivalent to
˙
x̄(t) = Āx̄(t) + P(t)B(t)u(t) (60)
−1
ȳ (t) = C (t)P (t)x̄(t) + D(t)u(t) (61)
Proof: Since
Ẋ (t + T ) = A(t + T )X (t + T ) = A(t)X (t + T )
Theorem 9
A q × p impulse response matrix G (t, τ ) is realizable if and only if G (t, τ )
can be decomposed as
Proof:
If G (t, τ ) is realizable, there exists a realization that meets (64).
Identifying M(t) = C (t)X (t) and N(τ ) = X −1 (τ )B(τ ) establishes the
necessary part of the theorem.
If G (t, τ ) can be decomposed as in (65), then the n-dimensional state
equation
W. Dong (UTRGV, Dept. of ECE) 71 / 75
Example
Consider g (t) = te λt or
g (t, τ ) = g (t − τ ) = (t − τ )e λ(t−τ )
−τ e −λτ
λt λt
g (t − τ ) = [e , te ]
e −λτ
−te −λt
0 0
ẋ(t) = x+ u(t)
0 0 e −λt
y (t) = [e λt , te λt ]x(t)